2015
DOI: 10.1016/j.pharep.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

HMG-COA reductase inhibitors: An opportunity for the improvement of imatinib safety. An experimental study in rat pulmonary hypertension

Abstract: Statins may intensify the beneficial effects of imatinib in PAH, which may be due to the additional influence of statin on the decrease of platelet-derived growth factor (PDGF)-induced effects. These properties allow the dose of imatinib used in PAH treatment to be reduced and thereby might improve its safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In our previous study we demonstrated rosuvastatin to exert a moderate impact on hemodynamics and RV hypertrophy in rats with MCT-induced PH. The mean RVP values (47.7 mm Hg) observed in MCT-induced rats receiving rosuvastatin at 10 mg/kg for 14 days were only 26.5% lower than those receiving the vehicle on day 29 of the experiment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study we demonstrated rosuvastatin to exert a moderate impact on hemodynamics and RV hypertrophy in rats with MCT-induced PH. The mean RVP values (47.7 mm Hg) observed in MCT-induced rats receiving rosuvastatin at 10 mg/kg for 14 days were only 26.5% lower than those receiving the vehicle on day 29 of the experiment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experimental results [ 22 ] show that rosuvastatin may exert only a moderate impact on hemodynamics or myocardial hypertrophy improvement in an MCT rat model. According to our knowledge, the effects of a combined statin and Rho kinase inhibitor regimen have not been assessed in PH.…”
Section: Introductionmentioning
confidence: 99%
“…between days 1 and 8 of pregnancy. 16 In Group 3, (Imatinib-40) 40 mg/kg imatinib was administered i.p. on the same days.…”
Section: Materials and Methods Animal Experiments And Drug Administrationmentioning
confidence: 99%
“… 48 A recent research confirmed that combination of statins with imatinib showed an enhanced effect in PH treatment, and statins can improve imatinib safety. 49 Combining drugs of different mechanisms to achieve greater therapeutic effects is beneficial for PH treatment. Therefore, combining statins with prostacyclin analogs, endothelin receptor antagonists, and phosphodiesterase type 5 inhibitors should be considered a possible therapeutic strategy.…”
Section: Possible Mechanisms Of Statins In the Treatment Of Phmentioning
confidence: 99%